Neuronal Cell Adhesion Molecules May Mediate Neuroinflammation in Autism Spectrum Disorder - Eve, Madeline; Gandawijaya, Josan; Yang, Liming; Oguro-Ando, Asami (Frontiers in Psychiatry, 2022)
Autism spectrum disorder (ASD) is a complex neurodevelopmental condition characterized by restrictive and repetitive behaviors, alongside deficits in social interaction and communication. The etiology of ASD is largely unknown but is strongly linked to genetic variants in neuronal Cell Adhesion Molecules (CAMs), cell-surface proteins that play a role in neuronal activity that support behavioral pathways in the brain. A combination of environmental and genetic factors are believed to contribute to ASD pathogenesis. Inflammation in ASD has been identified as one of these factors, demonstrated through the presence of proinflammatory cytokines, maternal immune activation and activation of glial cells in ASD brains. Glial cells are the main source of cytokines within the brain and, therefore, their activity is vital in mediating inflammation in the central nervous system. However, it is unclear whether the aforementioned neuronal CAMs play a role in modulating neuroimmune signaling or glial behavior. This review aims to address the largely unexplored role neuronal CAMs may play in mediating inflammatory cascades that underpin neuroinflammation in ASD, primarily focusing on the Nuclear Factor-κB (NF-κB), NOTCH and Mitogen-Activated Protein Kinase (MAPK) cascades. It will also investigate how neuronal CAMs may influence glial activity, associated with inflammation. This is important when considering the impact of environmental factors and the inflammatory response on ASD. Neuronal CAM1 (NCAM1) can regulate NF-κB transcription in neurons, directly altering proinflammatory signaling. Additionally, NCAM1 and Contactin-1 appear to mediate astrocyte and oligodendrocyte proliferation and in results, change the neuroimmune response. Importantly, although this review highlights the limited information available, there is evidence of a neuronal CAM regulatory role in neuroinflammatory signaling. This warrants further investigation into the role other neuronal CAM family members may have in mediating inflammatory cascades and would advance understanding of the neuroinflammation that contributes to ASD pathology.